REPRODUCTIVE PARAMETERS FOLLOWING ESTRUS SYNCHRONIZATION OF SANGAMNERI AND OSMANABADI GOATS - AMLE, M B; BIRADE, H S; GULAWANE, S U (The Indian Journal of Animal Reproduction, 2022)
Sangamneri (n=11) and Osmanabadi (n=7) breed goats (age, 2-4 yr; BW, 22-28 kg) subjected to estrus synchronization protocol (progestagen-impregnated intra-vaginal sponge for 7 days + Inj. eCG i.m. on the day of sponge removal) exhibited 100% estrus response with an earlier onset of estrus in Sangamneri breed (46.9± 2.5 vs. 24±6.23 h, p<0.05), longer duration of estrus in Osmanabadi breed (76.4±7.8 vs. 113.1±6.6 h, p<0.05) and similar conception rate in both the breeds (72.7% vs. 57.1%, respectively; p>0.05). Furthermore, out of pregnant goats, 62.5% Osmanabadi goats kidded and 8 kids were born; whereas, in Sangamneri breed, 50% goats kidded and gave birth to 2 kids. The litter size was higher (p<0.05) in Sangamneri (1.6) in comparison to Osmanabadi (1.0) goats. In brief, the reproductive parameters following estrus synchronization were better in Sangamneri compared to Osmanabadi goats.